2016
DOI: 10.3847/1538-4357/833/1/124
|View full text |Cite
|
Sign up to set email alerts
|

The Last Minutes of Oxygen Shell Burning in a Massive Star

Abstract: We present the first 4π-3D simulation of the last minutes of oxygen shell burning in an 18M supernova progenitor up to the onset of core collapse. A moving inner boundary is used to accurately model the contraction of the silicon and iron core according to a 1D stellar evolution model with a self-consistent treatment of core deleptonization and nuclear quasi-equilibrium. The simulation covers the full solid angle to allow the emergence of large-scale convective modes. Due to core contraction and the concomitan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
284
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 153 publications
(303 citation statements)
references
References 88 publications
18
284
1
Order By: Relevance
“…In the present study we found large-scale fluctuations of angular momentum in the convective helium zone of an evolved massive star, while the energy transport is similar to that expected from MLT, strengthening the validity of our simulation. Future studies will explore similar phenomena in silicon and oxygen shells (as done by, e.g., Mueller et al 2016)and effects of rotation (as done by, e.g., Chatzopoulos et al 2016).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…In the present study we found large-scale fluctuations of angular momentum in the convective helium zone of an evolved massive star, while the energy transport is similar to that expected from MLT, strengthening the validity of our simulation. Future studies will explore similar phenomena in silicon and oxygen shells (as done by, e.g., Mueller et al 2016)and effects of rotation (as done by, e.g., Chatzopoulos et al 2016).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Finally, it has been suggested that multi-dimensional effects in the convective burning shells at the onset of core collapse can have an effect on the NS kick amplitude (e.g. Burrows & Hayes 1996;Arnett & Meakin 2011;Müller et al 2016), i.e. precollapse asymmetries in the progenitor star could influence the asymmetry parameter of Eq.…”
Section: Ns Kick Magnitudes In Binariesmentioning
confidence: 99%
“…The initial explosion asymmetries that are intrinsically connected to the neutrino-driven explosion mechanism must therefore be included in self-consistent hydrodynamic 3D simulations of the SN blast wave from its initiation to the late stages of homologous expansion, if SN models shall be compared to the observational properties of SN explosions and SN remnants. These initial asymmetries can either grow stochastically from (small-scale) random fluctuations, or they might be triggered by large-scale asymmetries in the convective silicon and oxygen burning shells of the progenitor at the onset of core collapse (Burrows and Hayes, 1996;Arnett and Meakin, 2011;Couch and Ott, 2013;Müller and Janka, 2015;Müller et al, 2016b;Müller, 2016).…”
Section: Explosion Asymmetries and Large-scale Mixingmentioning
confidence: 99%
“…For example, they still lack sufficient (some more, some less) numerical resolution for convergence on the description of the turbulent flow in the postshock layer, employ a variety of (different) approximations for the 3D neutrino transport, omit important microphysics, obtain explosions only with special and not generally accepted assumptions such as rapid rotation or nonstandard modifications of the neutrino opacities (Melson et al, 2015a), and start from spherically symmetric initial conditions instead of the multidimensional flow that perturbs the convective burning shells around the iron core already prior to collapse Müller et al, 2016b;Müller, 2016). It is well possible that the neutrino mechanism will work well and can explain the observational properties (e.g., explosion energies and radioactive yields) for a wide range of massive progenitors once all these remaining deficiencies of current models have been removed.…”
Section: Supernovae Of Massive Iron-core Progenitorsmentioning
confidence: 99%